Pendampingan Inovasi Daur Ulang Galon Bekas Menjadi Pot Tanaman Sebagai Upaya Eco Masjid Ramah Lingkungan di Masjid Al-Kahfi Pandean - Anwar Fathoni; Achmad Ali Zahid; Mirza Abdullah (STAI Ma'had Aly Al-Hikam Malang, 2026)
Plastic waste, including used mineral water gallons, is a significant environmental issue in Indonesia. Mosques, as centers of Islamic civilization, have great potential to pioneer environmentally friendly movements through the Eco-Mosque concept. This study aims to implement and analyze the innovation of recycling used gallons into plant pots as a tangible strategy to realize an Eco-Mosque at Masjid Al Kahfi. The research method used was Participatory Action Research (PAR), which involved the mosque management and congregation. The program was carried out in several stages: (1) collection of used gallons, (2) pot creation, (3) production process (cutting, creating drainage, decoration), and (4) placement of the pots in the mosque area. Data was collected through observation and interviews. The results showed that this program successfully transformed 12 used gallons into functional and aesthetic plant pots, which subsequently adorned the mosque's courtyard and garden. It was concluded that this creative recycling innovation not only reduced plastic waste and beautified the environment of Masjid Al Kahfi but also successfully served as a powerful environmental education medium. Thus, it can become a model for other mosques to adopt and develop.